Platelet mitochondrial membrane potential in Parkinson's disease. (11th December 2014) - Antony, Paul M. A.; Boyd, Olga; Trefois, Christophe; Ammerlaan, Wim; Ostaszewski, Marek; Baumuratov, Aidos S.; Longhino, Laura; Antunes, Laurent; Koopman, Werner; Balling, Rudi; Diederich, Nico J.
Abstract Objective Mitochondrial dysfunction is a hallmark of idiopathic Parkinson's disease (IPD), which has been reported not to be restricted to striatal neurons. However, studies that analyzed mitochondrial function at the level of selected enzymatic activities in peripheral tissues have produced conflicting data. We considered the electron transport chain as a complex system with mitochondrial membrane potential as an integrative indicator for mitochondrial fitness. Methods Twenty‐five IPD patients (nine females; mean disease duration, 6.2 years) and 16 healthy age‐matched controls (12 females) were recruited. Live platelets were purified using magnetic‐activated cell sorting (MACS) and single‐cell data on mitochondrial membrane potential (∆ψ) were measured by cytometry and challenged with a protonophore agent. Results Functional mitochondrial membrane potential was detected in all participants. The challenge test reduced the membrane potential in all IPD patients and controls (P < 0.001). However, the response to the challenge was not significantly different between patients and controls. Interpretation While the reported protonophore challenge assay is a valid marker of overall mitochondrial function in live platelets, intact mitochondrial membrane potential in platelets derived from IPD patients suggests that presumed mitochondrial enzymatic deficiencies are compensable in this cell type. In consequence, mitochondrial membrane potential in platelets cannot be used as a diagnostic biomarker for nonstratified IPD but should be further explored in potential Parkinson's disease subtypes and tissues with higher energy demands.